2008
DOI: 10.1515/bc.2008.063
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an encapsulated ESAT-6-based anti-TB DNA vaccine and evaluation of its immunogenic properties

Abstract: Experimental preparations based on a DNA vaccine encoding the ESAT-6 antigen of Mycobacterium tuberculosis have been obtained (KpONE6) and studied for immunogenic effects in the murine model. The core of the preparation contains DNA of the recombinant plasmid pONE6 encapsulated within a spermidine-polyglucin conjugate, thereby protecting the DNA vaccine from degradation. KpONE6 induces a proliferative T-cell immune response in mice upon intramuscular immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Since IFN-g plays an important role in the induction of protective responses, its production is often used as a key indicator for evaluating the effectiveness of vaccines. IFN-g is produced by Th1-like cells, released early upon encapsulated CFP-10:ESAT-6-based anti-TB DNA vaccine T-cell activation, and in our experiment, increased levels of IFN-g were associated with stimulating splenocyte proliferation [27]. The increase in the IFN-g levels demonstrated a change toward the cellular immune response (Th1) in mice [28].…”
Section: Discussionsupporting
confidence: 53%
“…Since IFN-g plays an important role in the induction of protective responses, its production is often used as a key indicator for evaluating the effectiveness of vaccines. IFN-g is produced by Th1-like cells, released early upon encapsulated CFP-10:ESAT-6-based anti-TB DNA vaccine T-cell activation, and in our experiment, increased levels of IFN-g were associated with stimulating splenocyte proliferation [27]. The increase in the IFN-g levels demonstrated a change toward the cellular immune response (Th1) in mice [28].…”
Section: Discussionsupporting
confidence: 53%
“…Our rM.S-e6c10 vaccine expressed the ESAT6-CFP10 fusion protein in M. smegmatis as shown by Western blot. Interestingly, it induced higher levels of IFN-c and IL-2 than did ESAT6 or ESAT6-Flt (Flt3 ligand) [31,32]. This suggests a more intense cellular immunity response is induced by the fusion protein.…”
Section: Discussionmentioning
confidence: 95%
“…Recombinant BCG expressing ESAT-6 also conferred enhanced immunogenicity and protection against TB when compared with the parent BCG vaccine [29, 30]. Other vaccine platforms such as DNA vaccine [3133], Influenza virus [34], and Salmonella typhimurium [35] also demonstrated that ESAT-6 is a potential immunodominant antigen for the development of TB vaccines. In addition, a chimeric protein of Ag85A and ESAT-6 with strong immunogenicity showed a treatment effect on MDR-TB in mice [36, 37].…”
Section: Discussionmentioning
confidence: 99%